Two Spot Coupled Ring Resonators - Cuong, Nguyen Duy; Xuan Khoa, Dinh; Long Van, Cao; Canh Trung, Le; Dinh Thuan, Bui; Trippenbach, Marek (Communications in Physics, 2019)
Abstract. We consider a model of two coupled ring waveguides with constant linear gain and nonlinear absorption with space-dependent coupling. This system can be implemented in various physical situations as optical waveguides, atomic Bose-Einstein condensates, polarization condensates, etc. It is described by two coupled nonlinear Schrödinger equation. For numerical simulations, we take local two-gaussian coupling.It is found in our previous papers that, depending on the values of involved parameters, we can obtain several interesting nonlinear phenomena, which include spontaneous symmetry breaking, modulational instability leading to generation of stable circular flows with various vorticities, stable inhomogeneous states with interesting structure of currents flowing between rings, as well as dynamical regimes having signatures of chaotic behavior. This research will be associated with experimental investigation planned in Freie Universität Berlin, in the group of prof. Michael Giersig.